2004
DOI: 10.1177/154405910408300912
|View full text |Cite
|
Sign up to set email alerts
|

Mouth-opening Increases Upper-airway Collapsibility without Changing Resistance during Midazolam Sedation

Abstract: Sedative doses of anesthetic agents affect upper-airway function. Oral-maxillofacial surgery is frequently performed on sedated patients whose mouths must be as open as possible if the procedures are to be accomplished successfully. We examined upper-airway pressure-flow relationships in closed mouths, mouths opened moderately, and mouths opened maximally to test the hypothesis that mouth-opening compromises upper-airway patency during midazolam sedation. From these relationships, upper-airway critical pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 21 publications
(24 reference statements)
3
60
0
10
Order By: Relevance
“…Meurice et al [23] reported this phenomenon by measuring upper airway collapsibility in open-and closed-mouth positions in healthy sleeping volunteers and showed that sleeping with the mouth open increases upper airway collapsibility. In addition, Ayuse et al [24] tested the hypothesis that opening the mouth during sleep compromises upper airway patency during midazolam sedation by examining the relationship between pressure and flow in the upper airway in open-and closed-mouth positions. They concluded that maximal mouth opening increases upper airway collapsibility and can cause difficulties during midazolam sedation.…”
Section: Resultsmentioning
confidence: 99%
“…Meurice et al [23] reported this phenomenon by measuring upper airway collapsibility in open-and closed-mouth positions in healthy sleeping volunteers and showed that sleeping with the mouth open increases upper airway collapsibility. In addition, Ayuse et al [24] tested the hypothesis that opening the mouth during sleep compromises upper airway patency during midazolam sedation by examining the relationship between pressure and flow in the upper airway in open-and closed-mouth positions. They concluded that maximal mouth opening increases upper airway collapsibility and can cause difficulties during midazolam sedation.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that passive measurements of upper airway collapsibility in sedated subjects were similar to non-REM sleep (Ayuse et al, 2004; Inazawa et al, 2005; Ikeda et al, 2006). Active compensatory neuromuscular responses, however, have not been characterized in anesthetized subjects.…”
Section: Introductionmentioning
confidence: 81%
“…At each level of P N , breaths were evaluated for the presence of inspiratory airflow limitation, as previously described (Schwartz et al, 1988, 1989; Boudewyns et al, 2000; Ayuse et al, 2004). Inspiratory flow limitation was defined as the presence of a plateau in inspiratory airflow in association with a continued fall in esophageal pressure by at least 1 cm H 2 O beyond the onset of the plateau.…”
Section: Methodsmentioning
confidence: 99%
“…Decreased SpO 2 can be caused by occlusion of the upper respiratory tract following motion suppression, sedative drug overdose, or deep sedation 16 ; transient glossoptosis caused by choking or cough reflex 17 ; or the use of instruments such as those used for maintaining mouth opening during oral manipulations.…”
Section: Discussionmentioning
confidence: 99%